Tuna baitfish in the Indo-Pacific Region Proceedings of a workshop, Hoara, Solomon Islands, 11-13 December 1989 - Blaber, S.J.M. (ed.).; Copland, J.W. (ed.). (Canberra, Australia Australian Centre for Agricultural Research, 1990)
ACIAR Proceedings No. 30
Keywords: Indo Pacific; Baitfish; Tuna